Pengaruh Variasi Konsentrasi Asam Stearat Terhadap Stabilitas Fisik Sediaan Krim Tabir Surya Ekstrak Daun Sirih Hijau (Piper betle L.): The Effect Of Stearic Acid Concentration Variations On The Physical Stability Of Green Betel Leaf (Piper betle L.) Sunscreen Cream Preparations - Sartiman; Lathvi Masyithah (Universitas Gunadarma, 2025)
Exposure to ultraviolet rays at a certain level cannot be accepted by human skin. Objective: This study aims to see the potential value of the Sun Protection Factor (SPF) of green betel leaves (Piper betle L.) by finding good stability using stearic acid. Methods: This study was conducted with a qualitative approach with a laboratory experimental method. Data collection directly from the laboratory to determine whether there is sunscreen activity in green betel leaf extract (Piper betle L.) to see if there is a difference in the effect of stearic acid concentration on the stability of green betel leaf extract sunscreen cream (Piper betle L.). Results: The results obtained are that green betel leaf extract (Piper betle L.) has sunscreen activity with the higher the concentration of the extract, the higher the Sun Protection Factor (SPF) value. This can be proven by the results of data processing obtained, every 1% increase in concentration value. Then the SPF value increases by 0.21. The results of the stability test showed stable results with organoleptic consistency, pH, and homogeneity, and spreadability. After being formulated, the sunscreen cream has a Sun Protection Factor (SPF) value, the higher the concentration of stearic acid, the lower the SPF value, this can be proven by the results of data processing with the addition of 1% concentration value. Conclusion: The Sun Protection Factor (SPF) value decreases by -0.900 but the stability of the preparation shows good results. This study suggests that it is necessary to test the antioxidant levels in green betel leaf extract (Piper betle L.).